Perceptions of medical doctors and patients about imaging for people with low back pain: A qualitative study - Barbosa, Mariana M.; dos Santos, Anna Julia M.; Galli, Nilva; Vidal, Rubens V. C.; Grande, Guilherme H. D. [UNESP]; Oliveira, Crystian B. (Wiley, 2024)
Background: Low-value care is the use of substitutive/ineffective/harmful strategies based on available evidence, and it is considered one of the main contributors to the burden related to low back pain in health care systems. The use of routine imaging for patients with low back pain is the main example of inappropriate care. Therefore, understanding the perceptions of medical doctors and patients from Brazil about this practice may help propose strategies to reduce imaging rates. Objective: To investigate the perceptions of medical doctors and patients about imaging for the diagnosis of nonspecific low back pain. Design: A qualitative study using the framework analysis method. Settings: Primary and secondary care. Participants: Fifteen patients with low back pain and 15 doctors participated in this study. Data Collection: Sociodemographic data were collected from all participants, and the interviews were performed using a set of questions created based on the literature. Main Results: Patients and doctors believe that the main reason for ordering imaging tests is to identify the source of pain, and imaging could be useful for tracking disease progression over time or if there is a lack of improvement after treatment. Patients' expectations and pressures play a role in the decision to order imaging tests, but clinicians believe that education is the preferred strategy to reduce imaging rates. Conclusion: Identifying the source of pain, tracking the disease progression, and patients' expectations and pressures were the main drivers of imaging requests for low back pain. Educational strategies were suggested to reduce the use of routine imaging.